Security Implication of Crimes Committed by Police Officers, in Nairobi County, Kenya (Global Journal of Human-Social Science, 2025)
This study sought to examine the security implication of crime committed by police officers in Nairobi County This was necessitated by the fact that police officers have been committing crimes yet hardly any data has been collected maintained disseminated or made available to inform crime management The study assessed the nature of crimes committed by serving police officers recorded at the Milimani Criminal Courts between 2017 and 2020 and their implications on insecurity in Nairobi County established prevalence of crimes committed by dismissed police officers recorded at the Milimani Criminal Courts between 2017 and 2020 and their implications on insecurity in Nairobi County and established police officers perceptions on the relationship between the causal factors of crimes committed by police officers and insecurity in Nairobi County Kenya The study used mixed methods study design Questionnaires were used to collect data from 90 primary respondents and 30 Key informants Qualitative data was analyzed using content analysis and presented thematically using verbatim quotes
Keywords: crimes committed by police officers; recorded crimes; insecurity prevalence of crimes